2018
DOI: 10.1007/s10237-018-1030-y
|View full text |Cite
|
Sign up to set email alerts
|

Probing the effect of morphology on lymphatic valve dynamic function

Abstract: The lymphatic system is vital to the circulatory and immune systems, performing a range of important functions such as transport of interstitial fluid, fatty acid, and immune cells. Lymphatic vessels are composed of contractile walls and lymphatic valves, allowing them to pump lymph against adverse pressure gradients and to prevent backflow. Despite the importance of the lymphatic system, the contribution of mechanical and geometric changes of lymphatic valves and vessels in pathologies of lymphatic dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…Alternatively, the reductions in transport and pumping pressure could have been caused by changes in valve function resulting in an inability to maintain unidirectional flow and decreasing pumping capacity. We have shown that the valve length to vessel diameter ratio is an important determinant of pump efficacy 43 and thus an increase in vessel lumen diameter due to remodeling without a comparable increase in the valve length would reduce pump function. Under modest mechanical loading, the valves of isolated lymphatic vessel chains have been demonstrated to “lock” resulting in an inability to pump flow against an adverse pressure gradient 44 .…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, the reductions in transport and pumping pressure could have been caused by changes in valve function resulting in an inability to maintain unidirectional flow and decreasing pumping capacity. We have shown that the valve length to vessel diameter ratio is an important determinant of pump efficacy 43 and thus an increase in vessel lumen diameter due to remodeling without a comparable increase in the valve length would reduce pump function. Under modest mechanical loading, the valves of isolated lymphatic vessel chains have been demonstrated to “lock” resulting in an inability to pump flow against an adverse pressure gradient 44 .…”
Section: Discussionmentioning
confidence: 94%
“…Each leaflet is created from an intersecting plane between an axisymmetric vessel and a plane that cuts through the vessel at an angle (Ballard et al. 2018). Thus, the elastic leaflets are initially flat.…”
Section: Methodsmentioning
confidence: 99%
“…We recently conducted three-dimensional simulations using a fully coupled fluid–structure interaction model to probe the behaviour of compliant lymphatic valves in a fluid flow (Ballard et al. 2018). Valves with different geometries and mechanics were placed in a rigid axisymmetric vessel and flow was induced by applying oscillating or unidirectional pressure gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Primary lymphatic disorders are varied and the majority of reported cases do not have an identified mechanism. In most disorders, defects in relation to lymphatic valves are the cause of lymphatic dysfunction (Ballard et al, 2018). These patients generally present with bilateral lower limb lymphedema (e.g., Nonne-Milroy lymphedema, lymphedema praecox).…”
Section: Renal Lymphatic Physiology In Pathological Conditionsmentioning
confidence: 99%